Extrusion cooking effects on oxidative stability of oat coarse milling product - Gutkoski, Luiz Carlos; Dash, Ahmed Attia El (Pesquisa Agropecuaria Brasileira, 1999)
The objective of the present research was to study the effects of extrusion cooking on oxidative stability of oat (Avena sativa L.) milling product. The dehulled grains were ground in a Brabender Quadrumat Senior mill and separated in two fractions, coarse over 532 mm and fine less than 532 mm. The coarse fraction, with higher amount of crude protein, lipids and dietary fiber content was conditioned to moisture levels (15.5-25.5%) and extruded in a Brabender single-screw laboratory extruder (C/D= 20:1). The extrusion conditions were compression ratio of 3:1, screw speed of 100 rpm, a die of 6 mm in diameter and temperatures between 77.6 and 162.4°C in the 2nd and 3rd zones while the 1st zone was maintained at 80°C. The extruded material was dried, ground, conditioned in plastic bags and periodically determined the peroxide value and n-hexanal. The unsaturated fatty acids content of the oil of fraction was higher (79.47%). Independently of the initial moisture, all the products extruded at temperatures lower than 120°C showed low oxidative rancidity.